Ocena działalności zakładów ubezpieczeń w Nowej Zelandii - casus nadzoru publikacyjnego - Kurek, Robert (The assessment of an insurance company performance in New Zealand - a casus of publication supervision, 2006)
The article presents principles for insurance companies assessment performance in New Zealand. General conditions for insurance market functioning were characterised as well as its accompanying institutions. Self-regulatory attribute of the market becomes its peculiar feature, where the state does not pass over the control over its functioning to specific supervisory institutions, but transfers the control over insurance activities to the insured themselves by creating legal conditions facilitating practical performance of such control. Additionally there were described legal regulations referring to the assessment of life and not for life insurance companies functioning, where procedures related to obtaining rating assessment were emphasized.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 246-253